Preliminary Study on the Potential of Red Fruit Pigment (Pandanus conoideus) from West Papua as Dye-Sensitized Solar Cell (DSSC) - Stepanus, Jamius Bin; Patiran, Abdul Zaid; Sumarna, Sabir; Islam, Muh. Fajar (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The red fruit (Pandanus conoideus) is an endemic plant from Papua, known for its distinctive color and shape. This fruit is recognized for its bioactive properties, such as antioxidant, anti-inflammatory, and antihyperglycemic effects. Its high pigment content is believed to have potential as a sensitizer in DSSC applications. However, research on this topic remains underexplored. Therefore, the aim of this preliminary study is to investigate the potential of red fruit pigments for DSSC. The characterization of red fruit pigments was conducted through phytochemical screening, FTIR and UV-Vis spectral analysis, as well as literature reviews. Pigment extraction was carried out using maceration without involving drying or grinding processes. Phytochemical screening results revealed that the macerate contains flavonoids, alkaloids, phenolics and terpenoids, compounds commonly used as natural pigments in DSSCs. FTIR analysis showed the presence of functional groups such as carboxyl (-COOH), carbonyl (C=O), and hydroxyl (-OH), which can act as effective anchoring groups when interacting with nanosemiconductor surfaces. Meanwhile, UV-Vis analysis showed absorption peaks in the UV region (wavelength 204–399 nm) and the visible region (wavelength 400–550 nm). Based on literature studies and research findings, it can be concluded that the pigments in red fruit have potential applications as DSSC sensitizers.